Endovascular treatment of lead-related superior vena cava syndrome after pacemaker implantation - D. A. Feshchenko; K. V. Kaperiz; B. A. Rudenko; F. B. Shukurov; D. K. Vasiliev; K. V. Davtyan; A. V. Tarasov; Е. A. Trufanova; M. T. Taliouridze (Кардиоваскулярная терапия и профилактика)
Superior vena cava syndrome (SVCS) is due to impaired venous outflow from the head, neck, limbs and upper half of the body into the right atrium due to stenosis or complete obstruction of the superior vena cava (SVC). Increased venous pressure in the SVC and lack of timely treatment leads not only to serious complications, but also to death. In recent years, the etiology of SVCS has changed dramatically, mainly due to an increase in the number of implanted intravascular devices (central venous catheters, pacemakers, defibrillators, and other devices). Endovascular methods have become widely used in the treatment of patients with SVCS. This was primarily due to the minimally invasive nature of the intervention, the high technical success of the operation and the rapid onset of clinical improvement. Patients who develop SVCS after device implantation are predominantly younger and have a longer life expectancy. When choosing a treatment method, it is extremely important to take these factors into account and give preference to methods providing a long-term effect with the fewest possible complications. The article presents a case of endovascular treatment of a patient with SVCS occlusion, which developed 9 years after pacemaker implantation, using intravascular imaging methods.